2005
DOI: 10.1111/j.1600-0420.2005.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser photocoagulation for retinopathy of prematurity: structural and functional outcome

Abstract: ABSTRACT.Background: To report the structural and refractive outcome after laser photocoagulation for retinopathy of prematurity (ROP). Methods: Nineteen consecutive patients who had undergone photocoagulation for ROP between 1997 and 2002 at our clinic were examined for this noncomparative, consecutive, interventional, retrospective case series. A total of 37 eyes received either transscleral or transpupillary laser treatment. Data consisted of grade of ROP pre-and postoperatively, birth weight, perioperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 31 publications
(39 reference statements)
3
43
0
Order By: Relevance
“…The ET-ROP study emphasized that patients who require treatment should be treated within 48 h (8) . We found that treatment timing in the non-referred patient group was consistent with many previous studies and that treatment timing in the referred patient group was approximately 2 weeks later than the average of previous studies (23,24) . This situation may be a factor explaining the difference in success rate between the two groups.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The ET-ROP study emphasized that patients who require treatment should be treated within 48 h (8) . We found that treatment timing in the non-referred patient group was consistent with many previous studies and that treatment timing in the referred patient group was approximately 2 weeks later than the average of previous studies (23,24) . This situation may be a factor explaining the difference in success rate between the two groups.…”
Section: Discussionsupporting
confidence: 80%
“…According to the ET-ROP and CRYO-ROP study results, the threshold ROP was set to nearly 37 weeks in patients with BWs <1,251 g (8,22) . In several studies, patients were treated between 34 and 37 weeks, which may be the critical time interval for the progression of the ROP (23,24) . After establishing a diagnosis of ROP and identifying an indication for treatment, treatment should be immediately initiated.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be performed at a point in the natural history where vasoproliferation can be reversed, because once the vitreoretinal traction commences it is difficult to control the disease and prevent the retinal detachment with subsequent visual loss. 7 Knowing the progression of ROP in correlation with time is crucial for a correct screening. ROP usually does not develop within the first 2 weeks after birth.…”
Section: Timing Of the Laser Treatment For Ropmentioning
confidence: 99%
“…Therefore, ROP is understood as a two-phase process: an acute phase, generated by the relative hyperoxia of the extra-uterine environment, characterized by vaso-obliteration and non-vascularization of the anterior retina, and a chronic phase, defined by vasoproliferation. 7,8 The rationale for ROP treatment by laser photocoagulation is to destroy the non-vascularized retina to remove the source of the angiogenic factors, thus interrupting the pathogenic mechanism of the vasoproliferation and subsequent retinal detachment. 4,9 This was achieved for the first time in 1988 by cryotherapy, which proved its efficacy in preventing blindness caused by ROP.…”
Section: Rationale Of the Laser Treatment For Ropmentioning
confidence: 99%
“…It is accepted on the basis of clinical experience and the results of randomised trials that laser panretinal photocoagulation is an effective treatment for proliferative diabetic retinopathy [15][16][17] and that laser treatment is of benefit in controlling the neovascularisation that characterises the retinopathy of prematurity 18,19 and ischaemic branch retinal vein occlusion. 20,21 In spite of the fact that laser panretinal photocoagulation for diabetic retinopathy has been used since it was first suggested by Meyer-Schwickerath almost 50 years ago, 22 and that grid laser treatment in the management of macular oedema has been used for some 40 years, 23 some aspects of the mode of action of laser in these and similar conditions remain incompletely explained.…”
Section: Introductionmentioning
confidence: 99%